2023
DOI: 10.3390/machines11010057
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of High-Speed Electric Machines for Electric Vehicles: A Case Study of 100 kW V-Shaped Interior PMSM

Abstract: The need of compact machines increased in recent years due to increases in raw materials’ price. Hence, many studies are currently being conducted on high-speed challenges to propose an optimal design methodology. AC losses in windings are often not included in the optimization process and are treated in post-processing by choosing a suitable conductor’s diameter to mitigate skin and proximity effects. This paper presents an optimization and design methodology for high-speed electric machines considering these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This model is valid only when the slot is entirely and uniformly filled with conductors. Conditions concerning equivalence between DFEA and SFEA are given in [32].…”
Section: ) Hybrid Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model is valid only when the slot is entirely and uniformly filled with conductors. Conditions concerning equivalence between DFEA and SFEA are given in [32].…”
Section: ) Hybrid Modelsmentioning
confidence: 99%
“…To reduce computation time, an improved hybrid model was proposed [31] using a simple FEA model and considering 2D magnetic field with arbitrary waveform. Reference [32] proposes a new design and optimization methodology including proximity effect losses in the optimization process using simple FEA model. For losses due to circulating currents, a hybrid model [33] was developed using the induced voltage in each strand and applied to an interior permanent magnet synchronous machine (IPMSM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inevitable necessity of efficient eco-friendly products and machinery has paid the way for the development of electric vehicles. Various electric vehicle technologies are compared and suggested that the hybrid electric vehicle (HEV) is the most suitable one in terms of efficiency of operation, and reduced emission [1]. Also, due to the low availability of fossil fuel resources, the electrified vehicle has gained more importance [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of electric motors are used for HEVs, and they are listed in [3]. Generally, DC motors are less preferred because of the periodic maintenance of brushes and commutator segments [1]. Induction motors are used in Tesla cars due to their wide range of speed control, easy manufacturing, maintenance, and low cost, but they suffer from low power density, hence they are less preferred compared to synchronous motors [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%